SOSIALISASI PEMANFAATAN MINYAK JELANTAH UNTUK PEMBUATAN LILIN AROMATERAPI BAGI PELAKU USAHA IKM DI KABUPATEN WAJO - Arninda, Andi; Yusuf, Andi Asdiana Irma Sari; Tyassena, Flaviana Yohanala Prista (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2025)
The development of Small and Medium Enterprises (SMEs) in Indonesia continues to grow every year. In Wajo Regency, the development of SMEs is also increasing. Most SMEs use a lot of oil in their production processes. However, most of them have not utilized cooking oil from the food processing industry optimally, with many throwing it into the environment. This program was designed to enhance the awareness of SME entrepreneurs in Wajo Regency regarding the environmental hazards of cooking oil waste and its potential conversion into value-added products, such as aromatherapy candles. The initiative encompassed educational sessions, technical workshops, and live demonstrations of the candle-making process. The outcomes indicated a significant improvement in participants' understanding of waste cooking oil utilization and sustainable waste management strategies. Participants' feedback reflected an average satisfaction score exceeding 4, underscoring the program's effectiveness in delivering meaningful environmental solutions and practical benefits. Through this activity, it is hoped that not only can the participants utilize cooking oil waste in aromatherapy candles, but they can also use it in other products with added value.